LUDRUK JEMBER: RITUAL MASYARAKAT PERANTAUAN - Prasisko, Yongky Gigih (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
Abstract. Ritual in modern society means a tradition that is made to instill value through symbolic expression to the society. In this case, ludruk as a tradition related to the character of the society and region. In Surabaya, for example, ludruk also encourages the modernization of society in the context of modern cities. In Jember, ludruk is connected with the character of the overseas community, who try to overcome the cultural differences. This paper is based on field research with direct observation and interviews with cultural subjects. This paper seeks to see how the process of the formation of cultural subjects through their cultural role, in this case ludruk performance. Through Jember ludruk performance, overseas people from Java and Madura are trying to understand, experience and interpret the new environment which is different from where they came from. Laken Babad Djember and Sempolan is an effort to produce knowledge about Jember region. The second story of Babad is about the story behind the origin of the names of places in Jember. Ludruk Jember became the way overseas people from Java and Madura overcome cultural alienation through knowledge production. Ludruk Jember also became the home of culture, through which, the overseas people discovered the existence of their native culture: both Java and Madura, in Jember. Finally, as a ritual, Jember's ludruk plays a role in shifting from the original culture into Jember culture, which helped change the subject of the culture into Jember people.Keywords: Jember, ludruk, overseas, Babad, Java, Madura